Effect of Cooling Rate on the Characteristics of Eutectic Carbides in M2Al High-Speed Steel - Jianghua Xiang; Hui Yang; Changling Zhuang (Crystals)
The phase composition and morphological characteristics of eutectic carbides are key factors affecting the wear resistance and fatigue life of high-speed steel. In this study, a combination of experimental characterization and thermodynamic calculations was used to systematically reveal the dynamic regulation mechanism of cooling rate on eutectic carbides in M2Al high-speed steel. The results indicate that within a cooling rate range of 5 to 225 °C/min, the steel always contains a small amount of face-centered cubic-structured MC-type eutectic carbides and a large number of hexagonal close-packed structured M2C-type eutectic carbides. The three-dimensional morphology of MC-type eutectic carbides is smooth and rod-like, and is insensitive to the cooling rate, while the three-dimensional morphology of M2C-type eutectic carbides evolves from lamellar to dendritic with an increasing cooling rate. The increase in cooling rate significantly reduces the average size of eutectic carbides, increases the total area fraction, and improves the distribution uniformity. Additionally, the increase in cooling rate also promotes the significant refinement of secondary dendrites in M2Al high-speed steel, and the relationship between secondary dendrite arm spacing and cooling rate is <semantics>λSDAS=149.42⋅CR−0.39</semantics>. Finally, combining thermodynamic calculations with kinetic analysis, this study found that the formation of eutectic carbides is dominated by the segregation of elements such as V, Mo, and C during the final stage of solidification, while the chemical composition and three-dimensional morphological evolution of M2C-type eutectic carbides are synergistically controlled by the diffusion and competitive growth of elements such as W, Mo, and C in austenite. This study provides a theoretical basis for the solidification process and eutectic carbide control of M2Al high-speed steel.